2010
DOI: 10.1089/aid.2009.0198
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Structured Exercise Program on Nutrition and Fitness Outcomes in Human Immunodeficiency Virus-Infected Children

Abstract: The feasibility and effectiveness of a hospital-based exercise-training program followed by a home-based program for improving fitness, strength, and changes in body composition in children and adolescents with HIV were evaluated. Subjects participated in nonrandomized 24-session, hospital supervised exercise training program followed by an unsupervised home-based maintenance program. Outcome measurements included muscular strength=endurance, flexibility, relative peak VO 2 , body composition, and lipids. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
(28 reference statements)
2
30
2
6
Order By: Relevance
“…3 Thus, the pathological state may cause hypoactivity, which reduces fitness and functional capacity, leading to further hypoactivity. 3 In agreement with Miller et al, 2 our data showed that exercises are effective in increasing the levels of upper limb muscular endurance and flexibility of the lumbar spine and hamstring muscles. In the context of pediatric HIV, there is a need for interventions designed to improve fitness due to poor aerobic capacity, 22,23 flexibility, 23 anaerobic power, 24 agility and lower limb strength.…”
Section: 1517supporting
confidence: 91%
See 2 more Smart Citations
“…3 Thus, the pathological state may cause hypoactivity, which reduces fitness and functional capacity, leading to further hypoactivity. 3 In agreement with Miller et al, 2 our data showed that exercises are effective in increasing the levels of upper limb muscular endurance and flexibility of the lumbar spine and hamstring muscles. In the context of pediatric HIV, there is a need for interventions designed to improve fitness due to poor aerobic capacity, 22,23 flexibility, 23 anaerobic power, 24 agility and lower limb strength.…”
Section: 1517supporting
confidence: 91%
“…1 In children and adolescents living with HIV, only one study has demonstrated the feasibility, safety and efficacy of aerobic and resistive exercises to improve muscle strength and endurance, aerobic fitness and fat free mass. 2 This is important, since fitness is reduced in several pediatric pathological conditions and might be associated with premature mortality. .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They could stop the training further if they were not comfortable or faced any health issues. The above graph shows statistically significant in RPE after 6 weeks [17]. Aerobic exercise might contribute to the improvement of emotional status, increase the release of endogenous opioids and reduce the activity of the adrenocortical, pituitary and hypothalamic systems (ACPH) [18].…”
Section: Effect Of Aerobic Exercises On Quality Of Life Rate Of Percmentioning
confidence: 99%
“…26 Resultados similares foram encontrados em pacientes com faixas etárias distintas, sugerindo que tais benefícios independeriam da idade do praticante. 27,28 Apenas para ilustrar, dados ainda não publicados de nosso laboratório revelam que participantes do projeto de extensão Vida+ (exercício supervisionado para pacientes com HIV/AIDS) exibem melhores resultados para força isocinética e massa muscular relativa (Tabela 1) que pacientes sedentários alocados em grupo-controle. O índice de massa muscular relativa (IMM) é normalmente utilizado como ponto de corte para classificar idosos com risco de incapacidade física decorrente de moderada ou alta sarcopenia.…”
Section: Função Muscular E Síndrome De Wastingunclassified